2019
DOI: 10.1371/journal.pone.0215057
|View full text |Cite
|
Sign up to set email alerts
|

Elective pelvic irradiation in prostate cancer patients with biochemical failure following radical prostatectomy: A propensity score matching analysis

Abstract: Purpose To investigate whether whole pelvic radiotherapy (WPRT) improves biochemical relapse-free survival (bRFS) vs. prostate bed radiotherapy (PBRT) in prostate cancer patients receiving salvage radiotherapy (SRT) after radical prostatectomy. Methods Data from patients with prostate cancer who underwent SRT for biochemical recurrence between 2005 and 2012 in two academic institutions were retrospectively reviewed. Patients treated with WPRT in one hospital were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…SRT to the prostate bed alone, with no ADT, has historically been associated with 3–5-year rates of biochemical progression-free survival (bPFS) in the order of 50% [ 24 , 25 ]. The 5-year interim results of the recent NRG Oncology/RTOG 0534 SPPORT trial report higher rates of bPFS (71%), however, the threshold for biochemical failure was 2 ng/mL above the post-SRT [ 26 ] nadir compared to 0.2 ng/mL in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…SRT to the prostate bed alone, with no ADT, has historically been associated with 3–5-year rates of biochemical progression-free survival (bPFS) in the order of 50% [ 24 , 25 ]. The 5-year interim results of the recent NRG Oncology/RTOG 0534 SPPORT trial report higher rates of bPFS (71%), however, the threshold for biochemical failure was 2 ng/mL above the post-SRT [ 26 ] nadir compared to 0.2 ng/mL in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lawton et al, 22 whole-pelvis radiotherapy provides significant benefit to patients with regard to progression-free survival when delivered with neoadjuvant and concurrent hormonal therapy. Several other studies 10,18,32,35,36 have also demonstrated the benefit of whole pelvis radiotherapy in terms of biochemical-free survival. Aizer et al 16 conducted a study on whole-pelvis radiotherapy versus prostate-only radiotherapy in the management of locally advanced or aggressive prostate adenocarcinoma.…”
Section: Introductionmentioning
confidence: 91%
“…A study by Song et al investigated biochemical relapse-free survival in patients receiving whole-pelvis radiation therapy and reported a biochemical-free survival rate of 65.9% and concluded that patients undergoing radiation therapy after prostatectomy with whole-pelvis radiation therapy will have better biochemical relapse-free survival rates compared to prostate bed-only radiation therapy. 35 Poelaert et al 18 studied the outcome of whole-pelvis radiation therapy in patients with positive pelvic lymph nodes and reported an estimated biochemical relapse-free survival of 67%, a cancer progression-free survival of 71% and a cancer-specific survival of 96%. Furthermore, they reported that patients treated with whole-pelvis radiation therapy, along with androgen deprivation therapy, show a promising cancer-specific survival.…”
Section: Ptv Dose Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4,680 publications and 52 registered clinical studies were identified from the literature search, and 16 studies that met the eligibility criteria were finally selected, including 6 randomized controlled trials (RCTs) (7)(8)(9)(10)(11)(12) and 10 cohort studies (CRS) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Four studies that met the inclusion criteria were excluded because of no hazard ratio available for survival (33)(34)(35)(36).…”
Section: Included Studiesmentioning
confidence: 99%